Topological Structure of Generalized Rough Graphs - Sarmad, Samah; Yaqoub Yousif, Yousif (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The main purpose of this paper, is to introduce a topological space , which is induced by reflexive graph and tolerance graph , such that may be infinite. Furthermore, we offered some properties of such as connectedness, compactness, Lindelöf and separate properties. We also study the concept of approximation spaces and get the sufficient and necessary condition that topological space is approximation spaces.